How to identify and understand digital literacy among 9th grade Norwegian students: Examining the influences from school and home on students digital literacy - Ove E. Hatlevik (Universitetsforlaget, 2009)
Since 2003, the biennial national ITU Monitor survey has been carried out by the Network for IT Research and Competence in Education to gather information about the use of information and computer technology (ICT) in Norwegian schools, including students, teachers and school leaders. In the ITU Monitor 2009, the students were given an assessment to measure their digital literacy in addition to questions about when and how often they use ICT in school. The aim of this paper is to identify and understand how digital literacy among 9th grade students is related to time spent on computers at school and outside school, family background and priorities from the schools. The findings from the study reveal a large variation in digital literacy and this can indicate a digital literacy divide among the 9th grade students. Further, the results show how digital literacy is related to both school factors (e.g. access to computers and schools with an ICT-supportive climate) and home factors (e.g. family background and grades). Overall, the findings indicate how systematic factors at the individual and school levels have an impact on digital literacy.